2013
DOI: 10.1155/2013/243934
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D in Cardiometabolic Diseases

Abstract: Vitamin D deficiency is a highly prevalent condition. Low vitamin D levels have long been associated with bone diseases, such as rickets in children and osteomalacia and osteoporosis in adults. However, it has become apparent in recent years that adequate vitamin D levels are also important for optimal functioning of many organs and tissues throughout the body, including the cardiovascular system. Evolving data indicate that vitamin D deficiency is associated with an increased risk of cardiovascular disease (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 87 publications
2
45
0
1
Order By: Relevance
“…The appropriate concentration of vitamin D is important in many diseases, including abdominal obesity, type 2 diabetes mellitus, and dyslipidemia [3, 4]. It is believed that excessive body weight is a significant factor that leads to lower serum concentrations of the vitamin.…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate concentration of vitamin D is important in many diseases, including abdominal obesity, type 2 diabetes mellitus, and dyslipidemia [3, 4]. It is believed that excessive body weight is a significant factor that leads to lower serum concentrations of the vitamin.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also suggest that patients with coronary artery disease (CAD) have generally lower levels of Vitamin D compared to healthy population [2] although much heterogeneity in the results connecting Vitamin D to cardiovascular disease exists. Furthermore, both animal [4] and human [5,6] studies have reported associations between Vitamin D levels and cardiac function and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…These cytokines have the ability to inhibit lipoprotein-lipase, an enzyme responsible for hydrolyzing triglycerides (TG) and very low density lipoproteins (VLDL) to form fatty acids and glycerol, which leads to the elevation of TG and VLDL, and to a decrease in high density lipoproteins (HDL) [9]. Vitamin D has immuno-modulatory functions that regulate the production pro-inflammatory interleukins, and in this way counteracts the actions of these on the blood lipids [9,10].…”
Section: Introductionmentioning
confidence: 99%